A ICONOGRAFIA DE COMBATE ESPARTANA. A GUERRA NOS VASOS DE FIGURAS NEGRAS LACÔNIOS DO SÉCULO VI A.C. - de Moura, José Francisco (PHOÎNIX, 2020)
This article has for objectives to thinking about the role of war in laconian black-figure vases iconography of century VI b. C., understanding the specificities that characterize it.